Financial Management of Family Businesses Transparency - Compliance - Performance - Strategy - Governance - Zellweger, Thomas; Ohle, Patricio (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2023)
Financial management in family businesses is a special challenge. CFOs in particular are often at the crossroads of various interests and roles. However, not least the public reticence of family businesses has so far ensured that there is a lack of knowledge about these interrelationships. A specialist circle of CFOs from large German-speaking family businesses is dedicated at the Center for Family Business at the University of St.Gallen (Switzerland) to discuss these issues . In this book, these experts share their wealth of knowledge and experience with the public for the first time. Along a five-step model, they shed light on key areas of responsibility that go far beyond mere financial management. They discuss issues of transparency and compliance, from performance and strategy to governance - and provide concrete suggestions for everyday business life. Whether manager, owner, or advisory board member, anyone who bears responsibility in a family business can benefit from this bridge between theory and practice.The CFO network fbxperts.ch has also been present internationally since 3 years: in Italy, Spain, France, UK and other locations.
Part 1: remarks on the methodology of financial management from theory and practice -- From impact to insight - family business and financial leadership in practice and theory -- Five development stages of financial management of family businesses -- Part 2: transparency: kickstarter for transformation -- Optimal financing structure: avoid bottlenecks and maintain headroom with foresight: everything done right... Almost! -- Meaningful data for right decisions: how to achieve impact with data management -- The chief financial officer and the family office -- Generational wealth preservation: perspectives and fields of action -- The family office as a modern form of majordomus -- "structure follows strategy": from bean counter mode to aligning financial processes with strategy -- Optimising planning systems in a vuca environment -- A plea for more transparency: the fbxperts view -- Part 3: compliance - a "must" to avoid risks -- Internal control system also for family companies - the basis forproper management?! -- What people don't like to talk about: dealing with and defending against fraud -- Cyber attacks - company risk no.1 - underestimated by many -- Compliance is a must: the fbxperts view -- Part 4: performance: profit as the basis for self-financed growth -- Agility through digital transformation: it's high time -- Control systems and incentives as value drivers: separating financial objectives from action planning and control through a new control model -- Fostering and steering innovation -- Net working capital management in family businesses -- Performance must be managed: the fbxperts view -- Part 5: strategy: ensuring success and staying relevant for the customer -- Strategy development in family businesses -- Strategic planning in the family business: dealing with the principal-agent dilemma -- The m&a phenomenon in the context of family businesses: growth through acquisitions -- the m&a function in (family) businesses considering A frame of reference - observationsof a practitioner -- Internationalisation and digitalisation as a growth path -- Identifying "shifting" customer demand and megatrends: sustainable growth through a focus on the customer -- Sustainability as a competitive advantage and sustainable financial instruments for working capital financing (esg-linked) -- Strategy requires a balanced leadership team, feasibility check and good cooperation with the supervisory body: the fbxperts view -- Part 6: governance: the duty or the pleasure of leadership? -- Optimal board, decision-making processes and shareholder involvement -- Generational change and conflicts among shareholders -- Hr-strategy - from hire to fire -- Change in corporate culture as a driver of success -- Sustainable and long-term development of family businesses -- Good governance: the fbxperts view -- Part 7: conclusion: being able to leverage collective experiences -- The fbxperts view: a review of the five-step model and the "critical" challenges for family businesses - the genesis -- The value of experiential knowledge for complex decisions.
Keywords: Business enterprises -- Finance; Family-owned business enterprises; Strategic planning; Leadership; New business enterprises -- Finance; Accounting; Corporate Finance; Family Business; Business Strategy and Leadership; Entrepreneurial Finance; Accounting